Deterministic diffusion in a gravitational billiard - Basnarkov, Lasko; Urumov, Viktor (Oxford Academic, 2003)
Numerical study of the motion of a classical particle in a homogeneous gravitational field bouncing off elastically from a piecewise linear periodic boundary shows that it is characterized by diffusion constant, but nonlinear scaling of the mean-square displacement is also observed. It is shown that periodic by modulus trajectories cannot have a segment with vertical flight.